IMPROVING STUDENT LEARNING MOTIVATION BY USING COOPERATIVE LEARNING OF SNOWBALL THROWING MODEL ON SOCIAL SCIENCES SUBJECT AT TOPIC DIVERSITY OF ETHNIC AND CULTURAL OF INDONESIA AT SDN 055985 PEKAN SELESAI KAB. LANGKAT ACADEMIC YEAR 2017/2018 - Nurlia Ginting (VISION, 2018)
This study aims to determine the increase in student learning motivation through the cooperative learning of Snowball Throwing Model. This research was conducted and caused by the low motivation of social sciences learning on the topic of the diversity of ethnic and cultural of Indonesia in the grade V SD Negeri 055985 Pekan Selesai. The subjects of this study were all students of grade V SD Negeri 055985 Pekan Selesai in the odd semester of 2017/2018 academic year, amounting to 21 people. There were 8 male students and 13 female students. This research uses qualitative approach. This type of research is a class action research. The observed results of teachers observed during the study of significant improvements. Viewed from Cycle I, the results obtained are 55% and 65%. But the achievement is still not on the expected achievement. In Cycle II, 80% and 98% were obtained. The results of this study indicate that the interest of students in grade V SD Negeri 055985 Pekan Selesai has increased by 100% after following the study of ethnic diversity and cultural of Indonesia using a model of cooperative learning type snowball Throwing Model. This increase can be seen from the results of the questionnaire of students' learning cycle motivation I get an average of 69 increased student motivation motivation by 57% and cycle II obtained an average of 91 students increased learning motivation by 100%. Thus it can be concluded that there is an improvement in the results of teacher observation by using the cooperative learning type Snowball Throwing Model. In the second cycle of observation the researcher has changed and reached a high percentage level. Based on this result that by applying cooperative learning type of Snowball Throwing Model, so that the students' learning motivation on Social Sciences subject at topic of the diversity of ethnic and cultural of Indonesia in grade V SD Negeri 055985 Pekan Selesai increase and succeed.Keywords: Social Sciences, Cooperative Learning, Snowball Throwing Model